Manajemen Pengembangan Kurikulum dalam Mewujudkan Pendidikan Bermutu di Madrasah Ibtidaiyah Negeri (MIN) 1 Purbalingga - Siti Honiah Mujiati; Rita Sulastini; Sri Handayani (LPPM IAINU Kebumen, 2021)
This research aims to determine the Planning, Organizing, Implementing, and Controlling Curriculum Development in Realizing Quality Education at MIN 1 Purbalingga. This research is a qualitative research. Data collection uses interviews, observation, and documentation, and the validity of the data uses triangulation, and data analysis techniques include data collection, data reduction, data presentation, and conclusions drawing. This research resulted that: (1) Planning was carried out by holding a joint meeting to discuss curriculum development; (2) Organizing is carried out by forming a curriculum development implementation team; (3) Implementation is carried out through pre-instructional, instructional and follow-up activities; (4) Controlling is carried out through monitoring and evaluation activities. Supervision is carried out by the head of the Madrasah directly, unannounced inspections, and periodic, continuous, and comprehensive briefings. The activity of evaluating student learning outcomes is carried out by the teacher council through exams.